Interprofessional Teamwork and Collaboration Between Community Health Workers and Healthcare Teams - Catherine M. Franklin; Jean M. Bernhardt; Ruth Palan Lopez; Ellen R. Long-Middleton; Sheila Davis (SAGE Publishing, 2015)
Objectives: Community Health Workers (CHWs) serve as a means of improving outcomes for underserved populations. However, their relationship within health care teams is not well studied. The purpose of this integrative review was to examine published research reports that demonstrated positive health outcomes as a result of CHW intervention to identify interprofessional teamwork and collaboration between CHWs and health care teams. Methods: A total of 47 studies spanning 33 years were reviewed using an integrative literature review methodology for evidence to support the following assumptions of effective interprofessional teamwork between CHWs and health care teams: (1) shared understanding of roles, norms, values, and goals of the team; (2) egalitarianism; (3) cooperation; (4) interdependence; and(5) synergy. Results: Of the 47 studies, 12 reported at least one assumption of effective interprofessional teamwork. Four studies demonstrated all 5 assumptions of interprofessional teamwork. Conclusions: Four studies identified in this integrative review serve as exemplars for effective interprofessional teamwork between CHWs and health care teams. Further study is needed to describe the nature of interprofessional teamwork and collaboration in relation to patient health outcomes.